Value distribution of differential-difference polynomials of meromorphic functions - Zhang, R. R. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We obtain the results on the deficiencies of differential-difference polynomials. These results can be regarded as differential differenceanalogs of some classical theorems on differential polynomials. In particular, an exact estimate of the deficiency of some differential-difference polynomials is presented. We also give examples showing that these results are best possible in a certain sense.